Pathophysiology of Cardiovascular Complications in COVID-19 - Petrovic, Vladimir; Radenkovic, Dina; Radenkovic, Goran; Djordjevic, Vukica; Banach, Maciej (Frontiers in Physiology, 2020)
Numerous recent studies have shown that patients with underlying cardiovascular disease (CVD) are at increased risk of more severe clinical course as well as mortality of Covid-19. Also, the available data suggests that COVID-19 is related to numerous de novo cardiovascular complications especially in the older population and those with pre-existing chronic cardiometabolic conditions. SARS-CoV-2 virus can cause acute cardiovascular injury, as well as increase the risk of chronic cardiovascular damage. As CVD seem to be the major comorbidity in critically unwell patients with COVID-19 and patients often die of cardiovascular complications, we review the literature and discuss the possible pathophysiology and molecular pathways driving these disease processes: cytokine release syndrome, RAAS system dysregulation, plaque destabilisation and coagulation disorders with the aim to identify novel treatment targets. In addition, we review the pediatric population, the major cause of the cardiovascular complications is paediatric inflammatory multisystem syndrome that is believed to be associated with COVID-19 infection. Due to the increasingly recognized CVD damage in COVID-19, there is a need to establish clear clinical and follow-up protocols and to identify and treat possible comorbidities that may be risk factors for the development of cardiovascular complications.